An Inventory Model deteriorating itemswith Demand Dependent Production Rate under Permissible Delay Payment (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This paper considers a single supplier offering trade credit to demand a dependent productionrate with ramp type demand, which has not been reported in the literature. Previously, twoinventory models have been developed under the above conditions.Secondly, order quantity andreplenishment cycle time algorithms are designed to be optimized. Thefindings of the abovestudy show that lowering the production rate, decreasing the order insertion frequency anddecreasing the production rate leads to cost reduction, with no effect on the optimal solution aswell as demand-dependent production rates.The retailer will cut the replenishment cycle whenthe growth time is higher than the business loan; when it is small, within the maturity period ofthe goods, the optimal order cycle and the quantity of the optimal quantity will have no effect onthe trade credit. Finally, numerical examples are discussed to demonstrate sensitivity analysis ofoptimal solutions.